Selinunt, Italien: Die Arbeiten der Jahre 2014 und 2015 - Adorno, L.; Albers, Jon; Bentz, M.; Broisch, M.; Dally, Ortwin; Franceschini, M.; Miß, A.; Müller, J. M.; Schlehofer, Jenny; von Hesberg, Henner (e-Forschungsberichte des DAI, 2023)
The following paper delivers a report on material studies and field work in Selinunt 2014-15 including excavations in the kerameikos and new geophysical prospections.